Health education: the effectiveness of interventions in patients with heart failure - Ana Paula Dias de Oliveira; Agueda Maria Ruiz Zimmer Cavalcante; Camila de Souza Carneiro; Vinicius Batista Santos; Sue Moorhead; Juliana de Lima Lopes; Alba Lucia Bottura Leite de Barros (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: To evaluate the effectiveness of NIC interventions "Teaching: Disease Process", "Health Education" and "Cardiac Care" in the improvement of NOC results in individuals with Heart Failure (HF), and the Nursing Diagnosis (ND) "Ineffective Health Control". Methods: Retrospective cohort, conducted at a Health Education in Nursing outpatient clinic. Fourteen patients with HF had follow-up for one year in six bimonthly consultations. The effectiveness of interventions was verified through the change of the result scores through the Friedman's Non-Parametric Test and Analysis of Non-Parametric Variance for repeated measures. The level of significance was 5%. Results: The interventions were implemented in consultations in a variety of activities. There was a significant improvement in the result scores until the fourth visit (p<0.001). Conclusions: The interventions were effective in improving outcomes in patients with HF and Ineffective Health Control.